DEFLECTION ANALYSIS OF THE BUILDING STRUCTURE USING BUILDING INFORMATION MODELING: Case Study: Green House Display BRIN Cibinong Bogor - Yulianto Bastian Zai; Pio Ranap Tua Naibaho; Sampurna Bangun (International Journal of Multidisciplinary Research and Literature, 2023)
The National Research and Innovation Agency (BRIN) is currently carrying out the construction of research facilities in various regions in Indonesia, one of which is the construction of the Green House Display Facility Infrastructure located in the Cibinong Science Center and Botanical Garden (CSC-BG-LIPI) area. This study aims to model the structural elements of the BRIN Cibinong Bogor Green House Display building and conduct structural analysis of columns (K10, K11, K12) and beams (B3, B4, B10, B13, BP1, BP2) using Tekla Structures 21 and Tekla Structural. Designer 21. The result of this research is that the modeling of structural elements can be done well and in detail, for example, there are no structural components that have clashes. The largest maximum deflection occurs in beam B4 which is 0.004921 m. Based on the deflection calculation in article 24.2 of SNI 2847:2019, the maximum permit deflection value is 0.0125 m. This shows that all beams and columns analyzed meet the maximum allowable deflection requirements based on SNI 1726:2019 and SNI 2847:2019